In-Sacco Degradability of Various Legume-Tree Leaves from Limestone and Non-Limestone Areas in Malang - Hartutik (Hartutik); M. Soejono; Kustono (Kustono) (Buletin Peternakan, 1995)
Abstract dalam bentuk hard copy